213 A New Way of Memory Care in an Integrated Care HUB. (16th September 2019) - Murphy, Catherine; Cooke, John; Mulchay, Riona; Pope, George; Bolger, Maggie; Roche, Suzanne; O'Gorman, Millie; Brennan, Jacinta; Phelan, Niamh; Grant, Emma; Doyle, Marie
Abstract: Background: The Occupational Therapy (OT) service in the integrated care HUB team was established in January 2018. Prior to this, there was an established memory clinic, however with inconsistent access to OT. The streamlining and structuring of memory clinics further highlighted the need for post-diagnostic support for example individual sessions focusing on memory education and practical strategies to enable independence in daily activities. The integration of OT enabled person-centred strategies to be provided to individuals experiencing memory loss. Methods: A retrospective analysis was completed comparing the number of OT memory patient contacts between January to June 2018 and November 2018 to April 2019 also reflecting the memory care pathway developed during this period. OT assessed all new patients experiencing memory difficulties that impacted on functional activities to initiate referral process. In April 2018, the Memory Technology Resource Room (MTRR) opened and the OT HUB using to facilitate patient contacts. The design/implementation of cognitive rehabilitation groups in May 2018 added another step to pathway. Dementia cafés were established in public cafés in the city and county area, sponsored by local care provider, also supported by HUB team. Feedback was gathered from surveys given to individuals, carers and HUB team in the Café and MTRR. Results: From January to June 2018 there were 50 memory streamed patient contacts completed by the OT. From November 2018 to April 2019, 206 patient contacts were completed. These include both individual and group cognition focused sessions. Positive qualitative feedback was retrieved from attendees to MTRR and Café all indicating at least one positive outcome from post-diagnostic supports and services. Conclusion: A multi-domain cognitive OT service when initiated by an integrated care HUB proves to be an effective and acceptable memory care pathway. The development of this holistic pathway enabled the person to be seen in the right place, at the right stage of their journey with memory difficulties.